PENGARUH MEDIA ULARTANGGA TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS SDN 1 PARDAWARAS - Sari, Siska (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This research is motivated by of their problems in elementary school social strudies is the lck of demand by strudents. There are many factors that make strudent do not much like learning IPS because IPS that since the mterial contains more social topics that are rote, the methode or media is very helpful ketercapaiannyya a lesson. Thus the researchers to find out the influence of the of the media snake leader in improving learning outcomes of student in elementary school social strudies about the kindoms of Hindu-Buddhist in Indonesia. the method use in this research inquasi-experimental design with nonequivalent control grup. Instrumen use is the achievement test with multiple choice. From processing and data analysis conducted on differences in student learning outcomes using conventional learning model (classroom control) with the use of media snake leader (class experiment) proved there is a differencein the acquisition value of the posstest and the normal gain whice the class that use the conventional model in the category hight with a mean value of Ngain less effective. Ehereas the experimental class acquisitiom posttest value are at very hight category with a mean value of Ngain quite effective. It can be concluded on the use of media snake leader in SD Negeri 1 Pardawarasheavily influence the social studies students.